Urinothorax—An Underdiagnosed Cause of Acute Dyspnea: Report of a Bilateral and of an Ipsilateral Urinothorax Case. (16th October 2012) - Laskaridis, Leonidas; Kampantais, Spyridon; Toutziaris, Chrysovalantis; Chachopoulos, Basileios; Perdikis, Ioannis; Tahmatzopoulos, Anastasios; Dimitriadis, Georgios
Abstract : Urinothorax (UT) is a rare and often undiagnosed condition, defined as the presence of urine in the pleural cavity due to the retroperitoneal leakage of urine accumulation, known as urinoma, into the pleural space. UT usually is a transudative pleural effusion that presents in patients with obstructive uropathy and it may occur following surgical procedures in the ureter or kidney such as ESWL, PCNL, and URS. Its diagnosis requires a high degree of clinical suspicion since the respiratory symptoms tend to be absent or mild and the urological signs tend to dominate. However, UT may rarely present with severe and acute dyspnea as well. The objectives of this study are to describe two new cases of this rare entity, a bilateral case and an ipsilateral case focusing on the side that occurs according to the affected renal insult, and to alert the physicians to include UT in their differential diagnosis of pleural effusions especially in patients with recent urinary tract disorders.